2021
DOI: 10.3390/ijms22041813
|View full text |Cite
|
Sign up to set email alerts
|

Human Islet Microtissues as an In Vitro and an In Vivo Model System for Diabetes

Abstract: Loss of pancreatic β-cell function is a critical event in the pathophysiology of type 2 diabetes. However, studies of its underlying mechanisms as well as the discovery of novel targets and therapies have been hindered due to limitations in available experimental models. In this study we exploited the stable viability and function of standardized human islet microtissues to develop a disease-relevant, scalable, and reproducible model of β-cell dysfunction by exposing them to long-term glucotoxicity and glucoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…8, E and F). In accordance with previous studies ( 42 ), insulin content was reduced by exposing islet organoids to high glucose (fig. S12, A and B).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…8, E and F). In accordance with previous studies ( 42 ), insulin content was reduced by exposing islet organoids to high glucose (fig. S12, A and B).…”
Section: Resultssupporting
confidence: 93%
“…To assess whether PX-478 improves the function of human β cells under high metabolic workload, we performed experiments using human islet organoids. Similarly to what has been observed with human islets, prolonged exposure of human islet organoids to high glucose concentrations leads to a marked up-regulation of basal insulin secretion with the correspondent collapse of the stimulation index ( 41 , 42 ). However, when cultured at normal glucose concentrations, human islet organoids have the advantage, when compared to native human islets, to display higher responses to glucose in terms of insulin secretion ( 43 ).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…This is a difficult question to address in humans but is an important one to consider. The recent development of pancreatic islet microtissues by InSphero [ 129 ] may provide one platform in which this could be assessed. Islet microtissues pretreated with factors that enhance non-classical HLAI expression (and likely also classical HLAI) could be co-cultured with CD8 + T cell subsets with varying specificities to assess the impact this has on islet viability.…”
Section: Mediators Of Direct Beta Cell – Immune Cell Interactionsmentioning
confidence: 99%
“…In fact, transplantation of a sufficient number of islets to the ACE (75-300 islets in mice) showed that these islet grafts are capable of maintaining glycaemia in streptozotocintreated diabetic mice ( [1], reviewed in [2]). Islet organoids (also called pseudo-islets) that are formed by self-reassembly of islet cells following disaggregation and genetic manipulation, for example by adenoviral-mediated ectopic gene expression [3,4], behave similarly to native islets. Because of these features, we wanted to test the hypothesis that genetically engineered intraocular islet organoids can serve as production sites for blood-born proteins/peptides as a novel treatment strategy.…”
Section: Introductionmentioning
confidence: 99%